2019
DOI: 10.1002/lol2.10110
|View full text |Cite
|
Sign up to set email alerts
|

Headwater lakes and their influence on downstream discharge

Abstract: Small headwater lakes are common water features in northern environments. These small lakes are often reported to have an influence on downstream water quality; however, few studies have addressed the underlying hydrology of these systems and how small lakes influence downstream discharge or how far downstream these influences persist. We show that catchments with small lakes sustain baseflows compared to catchments without lakes. In addition, small lakes have limited influence on the magnitude and timing of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 36 publications
4
39
0
Order By: Relevance
“…Our assumption is further based on modelling studies of weathering rates in a soil transect in the Krycklan catchment, which indicates that there is a kinetic control of the release of BCs in the soils (Erlandsson et al, 2016). Since all BCs behave relatively conservatively in these environments (Ledesma et al, 2013;Lidman et al, 2014), we used their combined concentration as a proxy for soil contact time. However, the assumption is only valid when the water is in contact with mineral soils, not with peat in mires, which are abundant in some of the investigated sub-catchments.…”
Section: Linking Seasonal Base Cation Concentration and Isotopic Signature To Travel Times To Stream Watermentioning
confidence: 99%
“…Our assumption is further based on modelling studies of weathering rates in a soil transect in the Krycklan catchment, which indicates that there is a kinetic control of the release of BCs in the soils (Erlandsson et al, 2016). Since all BCs behave relatively conservatively in these environments (Ledesma et al, 2013;Lidman et al, 2014), we used their combined concentration as a proxy for soil contact time. However, the assumption is only valid when the water is in contact with mineral soils, not with peat in mires, which are abundant in some of the investigated sub-catchments.…”
Section: Linking Seasonal Base Cation Concentration and Isotopic Signature To Travel Times To Stream Watermentioning
confidence: 99%
“…Previous studies have the examined the spatial extent of lake influence on stream water characteristics. One such study used measurements of streamflow and water isotopes to examine the direct contributions of lake water to streams, and found that these contributions constitute a declining fraction of stream water across a distance from 1.4 to 4.2 km downstream of a lake (Leach & Laudon, 2019). An additional study examining sediment dynamics in a montaine stream‐lake network suggested that lakes act as sediment sinks, and thereby deplete the sediment content of lake outlet streams (Arp et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also examined temporal variations in the contributions of upstream lakes to stream water. Measurements of streamflow and water isotopes performed by Leach and Laudon (2019) estimated that these direct contributions of lake water to streams are greatest during periods of moderate to high discharge. This may seem contrary to our findings of higher stream temperature response to lakes are at low discharge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There should, therefore, be a significant relationship between the simulated travel times a nd the observed winter isotopic stream signature provided that the model performs well. Some of the sub-catchments are, however, affected by evaporation from lake surfaces that result in isotopic fractionation (Leach and Laudon, 2019). Th is fractionation must be accounted for in order to use the signature as a representation of the groundwater.…”
Section: Observations Of Stable Isotopesmentioning
confidence: 99%